(untitled) (Przegląd Religioznawczy – The Religious Studies Review, 2025)
Polish reflection on the subject indicated in the title remains relatively little known, particularly with respect to philosophical and social thought of the nineteenth and early twentieth centuries. In the present article, I shall confine myself to what I regard as the most essential issues, namely, the conceptualization of the relationship between science and religion in terms of conflict and coexistence. Within the intellectual debates of that period, this mode of framing the relation proved to be dominant. When referring to religion, I generally have in mind Christianity, and more specifically, the Roman Catholic Church. By science, I understand both the natural sciences and the social–humanistic disciplines. I approach these relations primarily as forms of tension arising between religious and scientific modes of cognition and knowledge, as well as between two distinct attitudes toward life, which depend, among other factors, on the perception of the world from the standpoint of faith or of science. This article does not aspire to offer an exhaustive analysis of the issue, even within such limited temporal boundaries. Its purpose is rather to reconstruct and critically examine selected positions representative of Polish philosophical and social thought of that era. Particular attention is devoted to the views of Adam Mahrburg, Ignacy Radliński, Alfred Dygasiński, Stefan Pawlicki, and Witold Rubczyński. The analysis aims not only to restore to contemporary debate voices that have hitherto remained marginal, but also to demonstrate their potential to inspire further reflection on the science–religion relationship within a pluralistic perspective.